Unpacking taste : the social life of wine - Waldin, Henrik Mikael (SLU/Dept. of Urban and Rural Development, 2022)
Wine’s context exceeds the story of pleasure and natural enchantment as it is also laden with conflict and controversy. Wine is part of contemporary discussions on globalization, class and postcolonialism, biodiversity and climate change. In a sense, wine does not only reflect nature, but wine also reflects and is embedded in its social context. The narrative of wine is technical, mythical, historical, and cultural all at the same time. A large part is communicated through relationships. Narratives are spread through actors such as importers, sommeliers, and journalists. These relationships have also become a framing force on the field of wine as knowledge has become widely available. All actors individually construe narratives altering them as they reach consumers. Importers and consumers shape groups through the market creating subfields such as natural wine. Natural wine started as a collective effort amongst small-scale actors to challenge the dominant discourse of conquering soil by technical effectiveness and instead reconnect and resonate with earth as a holistic system. This thesis establishes natural wine as a resistant force against the omnipresent consequences of modernity. Not a random cultural phenomenon but organized and deliberate. The success of natural wine on the market can be ascribed to how it correlates with a more general discourse on sustainability, environment, individualism, and a form of neo-romanticism. The narrative of being sensitive and connected to nature plays well with how consumerism demands goods to interplay with lifestyle choices. Wine is globalized and place bound at the same time. The connection to place and time make up the basis for traditions. Recent research is calling for regulation of the term “natural wine”. However, establishing regulations while being negligent of how natural wine is discursively defined amongst stakeholders may lead to discrepancy between perception and regulation, leading to unwillingness to comply amongst actors within the social field of wine. This thesis explores the context and relationships of actors within the wine industry and how the actors who make up these relationships influence, construct, and share narratives concerning wine. The aim is to create a deeper understanding of how wine is socially constructed and how relationships are created. The research is based on thick descriptions with perspectives of informants, the researcher’s observations from wine fairs, tastings, and travels in wine regions, as well as the contribution of narratives of wine literature. The intention is to concretize the social field of wine through an analytical lens of hermeneutics and structural phenomenology, disclose how external narratives influence informants and demonstrate how storytelling is constructed and construed through relationships to create an understanding of the reality that the modern vigneron operates in.